Gray Seal:Halichoerus grypus - Hall, Ailsa; Thompson, David (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2009)
This chapter discusses the characteristics, taxonomy, distribution, abundance, and ecology of the gray seal, or Halichoerus grypus. The gray seal is the only member of the genus Halichoerus. Its species name, grypus, means hook nosed, referring to the Roman nose profile of the adult male. Halichoerus means sea pig in Greek. On average, gray seal dives are generally short, lasting between 4 and 10 min with a maximum-recorded duration of about 30 min. Gray seal foraging is mainly confined to the shallow continental shelf waters. Typically, animals dive down to the seabed, in relatively shallow waters 60-100 m in depth but are capable of routinely diving to 200 m in some areas. Dives to more than 300 m have been recorded. Gray seals are highly successful predators of the North Atlantic. They feed on a variety of fish species and cephalopods. However, a large proportion of their diet is sand eels or sand lance (Ammodytidae), which can make up over 70% of the diet at some locations and in some seasons. Other prey includes whiting, cod, haddock, saithe, and flatfish (plaice and flounder). They are largely demersal or benthic feeders, and foraging trips lasting between 1 and 5 days away from a haul-out site are frequently focused on discrete areas that are within 40 km of a haul-out site. © 2009